Powerful Industrial Excimer Configured for High Altitude Water Vapor Measurements: A differential absorption lidar (DIAL) and a high‐power Raman lidar have been developed and optimized on Mount Zugspitze. Issue 1 (28th January 2019) - Delmdahl, Ralph; Emmerichs, Ulrich; Trickl, Thomas; Vogelmann, Hannes
Abstract: To improve the sensitivity and range of atmospheric water vapor measurements by ultraviolet Raman lidar, a powerful 308 nm industrial excimer laser was modified to deliver frequency‐stabilized, narrowline output with low divergence and linear polarization.